Temperature dependence of kinetic parameters related to oxygen electroreduction in acid solutions on platinum electrodes - Zinola Sánchez, Carlos Fernando (1994)
The oxygen electroreduction reaction (OERR) kinetics at (111)- and (100)-type Pt electrodes has been studied in aqueous 1.0 M H2SO4 solutions in the 8–62°C range. On both Pt electrodes and at all temperatures, two Tafel regions have been observed. The Tafel slope in the low current density range is −0.053 ± 0.005 V decade−1, irrespective of temperature and the surface texture of the electrode. For (111)-type Pt, the Tafel slope in the high current density range increases with temperature, approaching the −2.303(2RT/F) ratio, whereas for (100)-type Pt, it reaches a temperature-independent value equal to −0.165 ± 0.003 V decade−1. Temperature dependences of OERR Tafel slopes on both types of Pt electrodes offer the possibility of further insights into the mechanism of the reaction, through the interpretation of both the adsorption enthalpy and entropy of intermediates produced along the OERR. Compensation effects, involving activation enthalpy and entropy variations with the applied potential, are also considered to account for experimental data.